Preschool Attendance and Executive Function Mediate Early Academic Achievement Gaps in East Asia and the Pacific. Issue 8 (17th November 2018) - Sun, Jin; Zhang, Li; Chen, Eva; Lau, Carrie; Rao, Nirmala
ABSTRACT: Research Findings: This study investigated the relationship between family socioeconomic status (SES) and children's early attainment, and the roles of preschool attendance and executive function (EF) in this association. Participants were 3, 331 children (1, 584 girls) ranging in age from 36 to 71 months from Cambodia, Mongolia, and Vanuatu. Children's language, literacy, and mathematics attainment and EF were assessed using the East Asia-Pacific Early Child Development Scales. Mothers reported on family demographics and children's preschool experience. Results indicated significant associations between SES and academic attainment in all three countries. Further analysis showed that preschool attendance and EF were significant mediators of SES- related disparities in attainment, but differed by country. Both served as parallel and sequential mediators in the associations between SES and performance in language, literacy, and mathematics in Mongolia. However, only preschool attendance mediated the association of SES with literacy attainment in Cambodia, and only EF mediated that with children's mathematics and language performance in Vanuatu. Although SES is substantially related with early achievement in these developing countries, our findings indicate that preschool attendance and EF may attenuate this relationship. Practice or Policy :  Implications for the provision of early childhood education programs and public policy are discussed.